Effects of ambient temperature on influenza-like illness: A multicity analysis in Shandong Province, China, 2014–2017 - Yin, Jia; Liu, Ti; Tang, Fang; Chen, Dongzhen; Sun, Lin; Song, Shaoxia; Zhang, Shengyang; Wu, Julong; Li, Zhong; Xing, Weijia; Wang, Xianjun; Ding, Guoyong (Frontiers in Public Health, 2023)
Background The associations between ambient temperature and influenza-like illness (ILI) have been investigated in previous studies. However, they have inconsistent results. The purpose of this study was to estimate the effect of ambient temperature on ILI in Shandong Province, China. Methods Weekly ILI surveillance and meteorological data over 2014–2017 of the Shandong Province were collected from the Shandong Center for Disease Control and Prevention and the China Meteorological Data Service Center, respectively. A distributed lag non-linear model was adopted to estimate the city-specific temperature–ILI relationships, which were used to pool the regional-level and provincial-level estimates through a multivariate meta-analysis. Results There were 911,743 ILI cases reported in the study area between 2014 and 2017. The risk of ILI increased with decreasing weekly ambient temperature at the provincial level, and the effect was statistically significant when the temperature was <-1.5°C (RR = 1.24, 95% CI: 1.00–1.54). We found that the relationship between temperature and ILI showed an L-shaped curve at the regional level, except for Southern Shandong (S-shaped). The risk of ILI was influenced by cold, with significant lags from 2.5 to 3 weeks, and no significant effect of heat on ILI was found. Conclusion Our findings confirm that low temperatures significantly increased the risk of ILI in the study area. In addition, the cold effect of ambient temperature may cause more risk of ILI than the hot effect. The findings have significant implications for developing strategies to control ILI and respond to climate change.